Safety, Tolerability, and Pharmacokinetics of a Novel Mitochondrial Modulator, TRC150094, in Overweight and Obese Subjects: A Randomized Phase-I Clinical Trial - Joshi, Deepa; Jamadarkhana, Prashant; Kumbhare, Suchit; Singh, Amarinder; Kotecha, Jignesh; Bunger, Deepak; Shiwalkar, Ajay; Mohanan, Anookh; Dutt, Chaitanya (Frontiers in Pharmacology, 2021)
TRC150094, a novel mitochondrial modulator, can restore metabolic flexibility by improving insulin resistance in preclinical studies. This study primarily aims to evaluate the safety, tolerability, and pharmacokinetics (PK) of oral TRC150094 after conducting two double-blind, randomized, Phase-I studies, single ascending dose (SAD) and multiple ascending dose (MAD), with n = 46, in overweight/obese adult and elderly subjects. In addition, the effect of TRC150094 on pharmacodynamic (PD) efficacy markers was evaluated. PK assessments, including maximum concentration (Cmax), area under the plasma concentration (AUC), time to Cmax (Tmax), and elimination half-life (t½), were assessed at pre-specified time points. PD assessments included apolipoprotein B (ApoB), triglycerides, hepatic fat by magnetic resonance spectroscopy (MRS) and cardiopulmonary exercise testing (CPET) parameters. TRC150094 was rapidly absorbed, and the AUC of TRC150094 increased in a dose-dependent manner across all doses in non-elderly and elderly cohorts. Cmax was more than the dose-proportional for all doses in all cohorts. Tmax ranged from 0.25 to 4 h, and t½ ranged from 15 to 18 h, making TRC150094 suitable for once-daily dosing. Food did not interfere with the overall absorption of the drug. The metabolites of TRC150094 were glucuronide and sulfate conjugates, and 20% of the drug was excreted unchanged in the urine. TRC150094 at 50 mg showed an improving trend in triglycerides. A significant reduction in Apo B was observed after 50 mg dose (−2.34 vs. 13.24%, p = 0.008), which was, however, not the case after 150 mg (8.78 vs. 13.24%, p = 0.1221). Other parameters such as hepatic fat and insulin sensitivity indices (HOMA-IR, MATSUDA Index derived from OGTT) showed an improving trend for the dose of 50 mg. In terms of safety, all the AEs reported were mild to moderate in severity. None of the adverse events was considered definitely or probably related to treatment, and there were no abnormal laboratory findings. In conclusion, the PK of TRC150094 was linear with no clinically significant food effect. TRC150094 and its metabolites suggest a lesser likelihood of drug-drug interactions. Overall, TRC150094 ensured safety and exhibited suitability for all subjects. Clinical Trial Registration: EUDRA CT: 2009-014941-10 (SAD) and CTR-India registration: CTRI/2009/091/000601 (MAD)